Fatty acid composition of oil palm (Elaeis guineensis Jacq) fruits grown in Bangladesh - Uddin, MM; Yeasmin, MS; Jalil, MA; Rana, GMM; Rahman, ML; Alam, AKM S; Ibrahim, M (Bangladesh Journal of Scientific and Industrial Research, 2020)
This study was undertaken to evaluate the fatty acid composition and other physicochemical properties of oil palm (Elaeis guineensis) fruits grown in Bangladesh and compared these values with crude palm oil (CPO) imported from Malaysia. Ripe and fresh oil palm (Elaeis guineensis) fruits were collected from different districts of Bangladesh and the crude oils were extracted by a screw press machine and was divided into three fractions: crude palm oil (CPO), degummed palm oil (DPO) and degummed bleached palm oil (DBPO). The percent yield, their physico-chemical characteristics, fatty acid composition, β-carotene, tocopherols and tocotrienols of the fractions were determined. Fatty acid composition and other physicochemical properties of Bangladeshi crude palm oil (CPO) were found to be more or less similar to the CPO imported from Malaysia. Bangladesh J. Sci. Ind. Res.55(2), 153-158, 2020